Performance of modified multiple access scheme for DCSK - ZHOU Yi-gang1; SHI Ying1 (Tongxin xuebao)
Based on the time-delay-based multiple access DCSK,a modified TLMA-DCSK scheme was proposed. In the modified scheme,to reduce excessive interference,the reference samples occupied the different slots for different users,but the data samples occupied the same slots for all users. To compare with TLMA-DCSK,the performance was evalu-ated in terms of the bit error rate （BER） under AGWN channel model and multipath Rayleigh fading channel model. Theoretic analysis and simulation results show that the proposed scheme is better than TLMA-DCSK in BER.